Rancang Bangun Web E – Commerce berbasis CRM pada Nada Furnicraft Jepara (Information Technology and Telematics, 2015)
ABSTRACTFurnicraft is household equipment that is now a staple for every family . Purchasing furniture manually would take a long time and is less efficient , and therefore made the web that serves  to make sales online, so it will be easier for buyers when making purchases .The research objective is to design an e - commerce -based CRM that serves to conduct sales transactions online. System development methods used in the design of this system using a prototype method , whereas the system design using UML ( Unified Modeling Language ) . The software used in the design of online applications , among others, MySQL , PHP and XAMPP as a local server .This study will produce a web -based CRM that will allow customers to do online shopping . So will members of the ease and efficiency when purchasing goods.Keywords: furnicraft, online, prototype, php, mysql.